(Dis)continuity of African Indigenous knowledge. (March 2023) - Heto, Prince Paa-Kwesi; Mino, Takako
What role does Indigenous knowledge play in the lives of contemporary Africans? To investigate this question, we visited three communities in Ghana—rural, peri-urban, and urban—where we interviewed community members involved in communal education. Contrary to the literature on the decline of Indigenous knowledge, we find that Indigenous knowledge, practices, and institutions are resilient across all contexts. Traditional leaders continue to play a significant role as stewards of Indigenous knowledge despite the impact of colonization, rural–urban migration, and globalization. However, Indigenous knowledge does not exist in a vacuum. It coexists and competes with many knowledge systems, inculcating in Africans multiple identities and consciousness. We discuss the implication of our findings and explain why there is a need for Africans to better integrate their multiple consciousnesses and different lived realities.